Efficacy of high-performance vision training on improving the reaction time of collegiate softball athletes: A randomized trial - Feldhacker, D. R.; Molitor, W. L.; Althman, A.; Boell, M.; Kaiser, A.; Musch, A.; Willhite, L. (The Journal of Sports Medicine and Allied Health Sciences, 2019)
A well-developed visual system is integral to the dynamic nature of sport performance among collegiate athletes. Occupational therapists play an important role in addressing an athlete`s visual skills through incorporating meaningful occupation, in this case sport, into interventions while addressing specific client factors. The aim of the study was to examine the efficacy of occupational therapist led high-performance visual training in improving the reaction time of collegiate softball athletes. Method. A mixed method approach was used to collect both qualitative and quantitative data. Qualitative data were collected to assess athlete perceptions of sport, and quantitative data were collected using a mixed within group and between group design. Twenty-one participants were randomly allocated into two groups, each receiving a 6-week intervention which followed an evidence-based protocol. Group A consisted of Dynavision™ D2 training, and Group B of non-machine, therapist-led, visual training, twice weekly for 10-15 minutes each. Results. Results of the study highlight perceived meaningfulness of sport and display that both theory-based protocols were effective, as Group A and Group B experienced significant decreases in reaction time. However, decreases in reaction time were more significant for Group A in both proactive and reactive Dynavision™ D2 training modes. Conclusion. Results suggest that both the Dynavision™ D2 and alternative vision training as led by occupational therapists may be beneficial in improving the proactive and reactive reaction times of collegiate athletes, enhancing their abilities to participate in meaningful sports, but the Dynavision™ D2 may be a more effective training tool, especially related to proactive reaction time training.